Experimental and numerical investigation of the electro-mechanical response of particle filled elastomers - Part I: Experimental investigations - Mehnert, Markus; Faber, Jessica; Hossain, Mokarram; Chester, Shawn A.; Steinmann, Paul (European Journal of Mechanics A-Solids, 2022)
Electro-active polymers (EAPs) have the ability to undergo large deformations upon the stimulation by an electric field. They offer new design possibilities in a variety of applications, such as simple soft and flexible actuators, stretchable sensors, and energy harvesters. In the subclass of dielectric elastomers, the operation principle relies on the Coulomb forces between charged electrodes that deform the soft polymer. As the forces are dependent on the permittivity of the dielectric, the addition of filler particles with a high permittivity is a promising approach to increase the overall electro-mechanical coupling. This contribution presents the results of various mechanical and electro-mechanical experiments conducted with the silicone Elastosil P 7670TM filled with Barium-Titanate particles. These experiments are performed in such a fashion that the obtained results are well suited for the identification of the necessary material parameters of an electro-viscoelastic modeling approach in Part II of this contribution (Mehnert et al. Submitted).
Created from Fastlane, Scopus look-up
Keywords: Dielectric elastomers; Electro-active polymers; Electro-mechanics; Particle filled polymers